2019
DOI: 10.1016/j.ijid.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficacy of drug-resistant tuberculosis in Bashkortostan, Russia: A retrospective cohort study

Abstract: Background: Russia, together with other former Soviet Union countries, is characterized by one of the highest burdens of drug-resistant tuberculosis. Published data on the drug-resistant tuberculosis for these countries are limited, and it is not clear whether current treatment regimens remain effective against constantly evolving drug-resistant strains. Objectives: The aim of the study was to evaluate treatment efficacy of patients with multidrug-resistant (MDR), extensively drug-resistant (XDR) and drug-susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
7
3
Order By: Relevance
“…The mortality rate in our cohort was comparatively higher than the frequency of deaths observed among XDR-TB patients in Georgia (15.09%) (Frank et al, 2019), Estonia (17.54%) (Kliiman & Altraja, 2009) and Russia (23.61%) (Yunusbaeva et al, 2019), and lower than that observed in India (51.8%) (Prajapati et al, 2017) and South Africa (43 and 53%) (Pietersen et al, 2015;Yuengling et al, 2018). The relatively low mortality rate in the aforementioned studies could be due to the hiding of death by high LTUF rate ranging from 14.81 to 37.7% in these studies (Kliiman and Altraja, 2009;Frank et al, 2019;Yunusbaeva et al, 2019) as compared to 7.7% in our cohort. In the multivariate analysis, elderly patients (>60 years old) were significantly more likely to die.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The mortality rate in our cohort was comparatively higher than the frequency of deaths observed among XDR-TB patients in Georgia (15.09%) (Frank et al, 2019), Estonia (17.54%) (Kliiman & Altraja, 2009) and Russia (23.61%) (Yunusbaeva et al, 2019), and lower than that observed in India (51.8%) (Prajapati et al, 2017) and South Africa (43 and 53%) (Pietersen et al, 2015;Yuengling et al, 2018). The relatively low mortality rate in the aforementioned studies could be due to the hiding of death by high LTUF rate ranging from 14.81 to 37.7% in these studies (Kliiman and Altraja, 2009;Frank et al, 2019;Yunusbaeva et al, 2019) as compared to 7.7% in our cohort. In the multivariate analysis, elderly patients (>60 years old) were significantly more likely to die.…”
Section: Discussioncontrasting
confidence: 66%
“…In the present cohort, the treatment success rate (40.6%) was comparable with the global treatment success rate (39%) among XDR-TB patients (2016 cohort) (World Health Organization, 2018). However, it was better than the rates reported from Tajikistan (5.6%) (Makhmudova et al, 2019), Russia (12%) (Yunusbaeva et al, 2019), South Africa (4 and 31.4%) (Yuengling et al, 2018;Te Riele et al, 2019), China (14.6 and 30%) (Alene et al, 2017;He et al, 2017), India (25.9%) (Prajapati et al, 2017) and Georgia (33%) (Frank et al, 2019), and lower than the ones reported from Brazil (48.4%) (Gallo et al, 2018) and Argentina (65%) (Abbate et al, 2012).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Prolonged therapy is required for the toxic second-line anti-tuberculosis treatment which is burdensome for patient compliance [ 13 ]. This prolonged treatment with the less tolerated second-line anti-tuberculosis treatment regimen might have a lower rate of patient compliance with the treatment that could affect the outcome of therapy [ 15 , 16 ]. As a result, a lower rate of unfavorable outcome during the DR-TB treatment is a key component that indicates a successful outcome for the epidemic [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other potential risk factors such as diabetes, HIV infection, malnourishment, and silicosis can increase the risk of developing TB. Various studies have explored this issue and reported valuable results, including confirmation of the effects of HIV infection [9,10], low body mass index (BMI) [11], diabetes [12], smoking [13], poverty and malnourishment [14], and alcohol use on TB. Several studies have also reported that the risk of TB mortality was closely related to the presence of diseases such as HIV, silicosis, and diabetes, as well as individual and social characteristics [15,16].…”
Section: Introductionmentioning
confidence: 99%